Ernesto’s Journey of Individuation: A Jungian Analysis of José María Arguedas’s Los ríos profundos - Herrera Bejines, Luis Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper explores the journey of individuation of Ernesto, the main character of Los ríos profundos (1958), written by José María Arguedas. By applying the Jungian literary theory, one can see the process of individuation in Ernesto as he progresses through the novel. As Ernesto begins his transition from the Andean world to the Western world, he also crisscrosses from his collective unconscious to his consciousness. His journey exhibits the painful but exciting journey between the two realms of the psyche. Arguedas presents the following five Jungian archetypes in many ways and on many levels in this novel: persona, ego, shadow, anima and self. The process of individuation is not only an inner journey for Ernesto, it is also a learning process, which allows his maturation. This essay explores Los ríos profundos, a “literature of migration,” as Antonio Cornejo Polar (1998) has denominated Arguedas’s work, and “literature of growth,” as Luis Harss (1983) and Ariel Dorfman (1980) discuss in their articles, while focusing on the journey of Ernesto and incorporating a Jungian literary perspective.